HISTORIES AND RUPTURES IN PLATFORM GOVERNANCE - Guarna, Tomás; de Keulenaar, Emillie; Gibson, Anna; Liu, Diyi (AoIR Selected Papers of Internet Research, 2026)
Scholars of platform governance, referring to dynamic relationships between governments, platform companies, and civil society, have often inquired about the new ways that online activity is structured through emerging technologies, norms, and political tensions. At the same time, we recognize a need to historicize these power relations: tracing the continuities, reconfigurations, and above all ruptures among “novelties”. This panel brings together four papers that advance the historicization of platform governance. Two papers explore “prehistories” of content moderation in eBay and in CompuServe's CB Simulator, looking specifically at how moderation responded to commercial and political pressures as opposed to idealistic visions of unregulated online spaces. The other two papers offer recent analyses of contemporary ruptures in platform governance, one examining how media governance approaches historically shape platform regulation in Indonesia and Pakistan and another investigating the shift from simple adjudication to complex forms of mediation and consensus-building. Juxtaposing prehistories with contemporary analyses sheds light on how moderation challenges, tensions, and “solutions” have diminished and persisted.